Regional performance targets for transparent near-infrared switching electrochromic window glazings - Nicholas DeForest; Arman Shehabi; Guillermo Garcia; Jeffery B. Greenblatt; Eric R. Masanet; Eleanor S. Lee; Stephen E. Selkowitz; Delia J. Milliron (Building and Environment, 2013)
With building heating and cooling accounting for nearly 14% of the national energy consumption, emerging technologies that improve building envelope performance have significant potential to reduce building energy consumption. Actual savings from these technologies will depend heavily upon their performance in diverse climate and operational conditions. In many cases, early-stage research can benefit from detailed investigation in order to develop performance thresholds and identify target markets. One example, a dynamic, highly transparent, near-infrared switching electrochromic (NEC) window glazing, is the focus of this investigation. Like conventional electrochromics, the NEC glazing can dynamically tune its optical properties with a small applied voltage. Consequently, the glazing can block or transmit solar heat to reduce cooling or heating loads, respectively. Unlike conventional electrochromics, NEC glazings remain transparent to visible light, causing no adverse effect to daylighting or building aesthetics. This study utilizes the software COMFEN to simulate a broad range of NEC performance levels, for commercial and residential buildings in 16 climate-representative reference cities. These simulations are the basis for identifying performance levels necessary to compete with existing static technologies. These results indicate that energy savings are strongly influenced by blocking-state performance. Additionally, residential applications have lower performance requirements due to their characteristic internal heat gains. Finally, the most dynamic NEC performance level is simulated in competition with high performing static alternatives. Here heating and cooling energy savings range from 5 to 11 kWh/m2 yr for commercial and 8–15 kWh/m2 yr for residential, in many regions on the order of 10%.
Keywords: Dynamic windows; Electrochromic glazings; NIR-switching; Performance targets; Solar heat gain

U.S. energy savings potential from dynamic daylighting control glazings - Arman Shehabi; Nicholas DeForest; Andrew McNeil; Eric R. Masanet; Jeffery B. Greenblatt; Eleanor S. Lee; Georgeta Masson; Brett A. Helms; Delia J. Milliron (Energy and Buildings, 2013)
Daylighting controls have the potential to reduce the substantial amount of electricity consumed for lighting in commercial buildings. Material science research is now pursuing the development of a dynamic prismatic optical element (dPOE) window coating that can continuously readjust incoming light to maximize the performance and energy savings available from daylighting controls. This study estimates the technical potential for energy savings available from vertical daylighting strategies and explores additional savings that may be available if current dPOE research culminates in a successful market-ready product. Radiance daylight simulations are conducted with a multi-shape prismatic window coating. Simulated lighting energy savings are then applied to perimeter floorspace estimates generated from U.S. commercial building stock data. Results indicate that fully functional dPOE coatings, when paired with conventional vertical daylight strategies, have the potential to reduce energy use associated with U.S. commercial electric lighting demand by as much as 930 TBtu. This reduction in electric lighting demand represents an approximately 85% increase in the energy savings estimated from implementing conventional vertical daylight strategies alone. Results presented in this study provide insight into energy and cost performance targets for dPOE coatings, which can help accelerate the development process and establish a successful new daylighting technology.
Keywords: Clerestories; daylighting; Dynamic prismatic optical elements (dPOE); energy efficiency; Glare; indoor environmental quality; radiance; windows